Predicting moral intelligence in nursing students and its relationships with self-compassion, and cultural competence: a cross-sectional study - Monir Nobahar; Sajad Yarahmadi; Nayyereh Raiesdana; Elham Shahidi Delshad; Fatemeh Hajizadegan; Farzad Ebrahimzadeh (BMC, 2022)
Abstract Background In the recent era, nursing needs employees with moral intelligence, cultural competence, and self-compassion skills more than ever. This study aimed to determine the predictors of moral intelligence and its relationship with self-compassion and cultural competence in nursing students. Methods This cross-sectional and multi-center descriptive study was conducted in 2022. With convenience sampling, 250 nursing students from three Iranian universities participated in this study. Data gathering included the Moral Intelligence Questionnaire, Self-Compassion Scale (short form), and Cultural Competency Questionnaire. The data were analyzed using descriptive statistics, the correlation between variables, and hierarchical regression. Results The results showed that nursing students had good moral intelligence (72.63 ± 11.38), moderate self-compassion (37.19 ± 5.02), and poor cultural competence (50.06 ± 13.15). No statistically significant relationship was observed between self-compassion and cultural competence (r = 0.11, p = 0.07). Moral intelligence with marital status (r = 0.16, p = 0.01), academic year (r = 0.14, p = 0.03) and self-compassion (r = 0.33, p < 0.001) had a significant relationship in such a way that these variables explained 15% of moral intelligence and self-compassion had the highest impact (p < 0.001). Conclusion Considering the moderate level of self-compassion and the poor level of cultural competence reported in the undergraduate nursing students, and also that self-compassion was known to be a predictive factor for moral intelligence, planners and educators must pay more attention to promoting self-compassion and cultural competency in the curriculum and conduct studies to find ways to improve them.